THERMAL CONSOLIDATION OF SOFT BANGKOK CLAY - H. M. Abuel-Naga; D. T. Bergado; S. Soralump; P. Rujivipat (International Association of Lowland Technology, 2005)
Understanding the thermo-mechanical behavior of saturated fine grained soils has become a very important topic whenever the geotechnical problems involve thermal effects. Previous research works in literature show that by subjecting the saturated fine-grained soils to temperature less than water boiling point volumetric and shear strength changes are induced. The thermally induced changes have been attributed to the physico-chemical change at the microscopic level. The aim of this research is to study the thermo-mechanical behavior of natural soft Bangkok clay, with temperature up to 90OC. Intensive laboratory tests using modified oedometer apparatus were conducted to investigate this behavior. The testing program was directed to study the effect of heat on the thermally induced volume change at different temperature and stress conditions, the thermal evolution of the preconsolidation pressure, the induced overconsolidation behavior after heating/cooling cycle, and the effect of temperature on the hydraulic conductivity. The experiments carried out on soft Bangkok clay provided some additional useful data on the thermo-mechanical behavior of the soft deposits. The results of this research work have been compared with those in literature with different clay types to generalize the thermo-mechanical behavior of the saturated clays.